Becoming-Plant: Post-Human Ethics and The Refusal of Flesh in Han Kang’s The Vegetarian - Sushil Ghimire, (Journal of Balkumari College, 2025)
In today’s world, human identity is influenced by political control over bodies, environmental problems, and physical acts of resistance. Han Kang’s novel The Vegetarian (2015) tells the story of Yeong-hye, a woman who decides to stop eating meat. Over time, she begins to reject not only food but also her role in human society, choosing instead to live like a plant.This study investigates how the novel enacts a post-human ethical position by dismantling traditional humanist notions of agency, language, and autonomy. The aim of this study is to explore The Vegetarian through the lens of post-human ethics, particularly examining how the protagonist Yeong-hye’s bodily withdrawal represents a radical refusal of normative human subjectivity. Drawing upon the theoretical frameworks of Rosi Braidotti and Donna Haraway, this paper adopts a qualitative, close-reading methodology to analyze Yeong-hye’s silent dissent as a mode of becoming that challenges patriarchal, anthropocentric, and consumerist structures. The study utilizes Braidotti’s concept of “becoming-other” and Haraway’s critique of human exceptionalism to argue that Yeong-hye’s transformation is not madness or passivity but a deliberate ethical disruption—one that critiques the violence of normative embodiment. Her journey toward plant-life becomes a mode of resistance that is both ecological and existential. The Vegetarian is uniquely positioned to address the intersection of gender, body, and post-human transformation. In a narrative where the protagonist says little yet expresses everything through her physical metamorphosis, the novel becomes a profound meditation on how silence, withdrawal, and nonhuman identification can reframe our understanding of ethics, suffering, and refusal.